2018
DOI: 10.1111/acem.13523
|View full text |Cite
|
Sign up to set email alerts
|

A Case–Control Study of Sonographic Maximum Ovarian Diameter as a Predictor of Ovarian Torsion in Emergency Department Females With Pelvic Pain

Abstract: A threshold MOD of 5 cm on pelvic ultrasound may be useful to rule out ovarian torsion in postmenarchal females presenting with lower abdominal and pelvic pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 28 publications
2
30
0
Order By: Relevance
“…With regards to imaging, 98 (88%) of our emergency AT cases had any imaging (ultrasound or computed tomography) pre-operatively. Of them, 80 had doppler ows reported of whom 28 (35%) had normal ows, similar to published pre-operative diagnostic rates of 36.6-55.8% [5,15,23]. Other studies have found that ultrasound (US) diagnosis of AT has low sensitivity 70% and speci city 87% [24], where abnormal dopplers only have 61% sensitivity and 98% speci city [23].…”
Section: Discussionsupporting
confidence: 75%
“…With regards to imaging, 98 (88%) of our emergency AT cases had any imaging (ultrasound or computed tomography) pre-operatively. Of them, 80 had doppler ows reported of whom 28 (35%) had normal ows, similar to published pre-operative diagnostic rates of 36.6-55.8% [5,15,23]. Other studies have found that ultrasound (US) diagnosis of AT has low sensitivity 70% and speci city 87% [24], where abnormal dopplers only have 61% sensitivity and 98% speci city [23].…”
Section: Discussionsupporting
confidence: 75%
“…As a predictor of ovarian torsion, there is a report that the maximum ovary diameter is 50 mm. The sensitivity when the threshold was 50 mm was 91% (83-97%) [9], and in this case, it was also suspected to be ovarian torsion based on the size of the right ovary.…”
Section: Discussionmentioning
confidence: 72%
“…Oltmann et al and Budhram et al reported that there is more likelihood of torsion when the size of the ovarian mass is 5 cm or larger [ 18 , 19 ]. In the present study, there were 17 cases (60.71%) having 5-10 cm size of adnexal mass which had undergone torsion.…”
Section: Discussionmentioning
confidence: 99%